2023
DOI: 10.3389/fnut.2023.1089972
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional risk and a high NRS2002 score are closely related to disease progression and poor prognosis in patients with COVID-19

Abstract: BackgroundOrganism can lead to excessive nutrient consumption in the infected state and increase nutritional risk, which is detrimental to the control of the infection and can further aggravate the disease.ObjectivesTo investigate the impact of nutritional risk and the NRS2002 score on disease progression and prognosis in patients with COVID-19.MethodsThis was a retrospective cohort study including 1,228 COVID-19 patients, who were divided into a with-nutritional risk group (patients with NRS2002 score ≥ 3) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(40 reference statements)
1
2
0
Order By: Relevance
“…In the post epidemic era, breakthrough infections of SARS-CoV-2 are being increasingly observed worldwide due to the high pervasiveness of viral spread, the emergence of novel variants (11), progressive ease of restrictive measures and waning protection against infection. In this retrospective study, we found that the critical illness rate was 2.8%, and the mortality rate was 0.5%, both of which were low, which was consistent with our previous report (16)(17)(18)(19). We also found that the immune breakthrough rate in this study cohort was 27.2%, with 4.8% of patients having previous infections, 22.4% of patients having been vaccinated, and only 6% of patients having been fully vaccinated.…”
Section: Discussionsupporting
confidence: 92%
“…In the post epidemic era, breakthrough infections of SARS-CoV-2 are being increasingly observed worldwide due to the high pervasiveness of viral spread, the emergence of novel variants (11), progressive ease of restrictive measures and waning protection against infection. In this retrospective study, we found that the critical illness rate was 2.8%, and the mortality rate was 0.5%, both of which were low, which was consistent with our previous report (16)(17)(18)(19). We also found that the immune breakthrough rate in this study cohort was 27.2%, with 4.8% of patients having previous infections, 22.4% of patients having been vaccinated, and only 6% of patients having been fully vaccinated.…”
Section: Discussionsupporting
confidence: 92%
“…This model holds tremendous potential in the realms of prediction, prevention, and personalized medicine for the elderly, particularly as the global elderly population continues to grow, posing challenges to healthcare resources and economic burdens. Prior research mainly focuses on exploring the progress and prognosis of the disease to reduce mortality [ 24 , 25 ]. However, few studies have predicted all-cause mortality in community-dwelling older adults.…”
Section: Discussionmentioning
confidence: 99%
“…For older adults and critically ill patients with multiple underlying diseases, early initiation of enteral and parenteral nutrition support can effectively protect the intestinal mucosal barrier and immune function, reduce the incidence and mortality of infectious complications. [12][13][14] Therefore, timely and standardized nutritional support can effectively improve the nutritional status, immune function, and clinical outcomes of COVID-19 infection, 15 promote recovery and reduce the risk of recurrence, 16,17 improve patient survival and quality of life. Therefore, how to quickly and accurately foresee the risk factors of COVID-19 "re-positive" in malnourished older adults is a clinical problem that needs to be solved urgently.…”
Section: Introductionmentioning
confidence: 99%